Antidiarrheal efficacy and cellular mechanisms of a Thai herbal remedy. - Lukmanee Tradtrantip; Eun-A Ko; Alan S Verkman (Public Library of Science (PLoS), 2014)
Screening of herbal remedies for Cl(-) channel inhibition identified Krisanaklan, a herbal extract used in Thailand for treatment of diarrhea, as an effective antidiarrheal in mouse models of secretory diarrheas with inhibition activity against three Cl(-) channel targets. Krisanaklan fully inhibited cholera toxin-induced intestinal fluid secretion in a closed-loop mouse model with ∼50% inhibition at a 1 ∶ 50 dilution of the extract. Orally administered Krisanaklan (5 µL/g) prevented rotavirus-induced diarrhea in neonatal mice. Short-circuit current measurements showed full inhibition of cAMP and Ca(2+) agonist-induced Cl(-) conductance in human colonic epithelial T84 cells, with ∼ 50% inhibition at a 1 ∶ 5,000 dilution of the extract. Krisanaklan also strongly inhibited intestinal smooth muscle contraction in an ex vivo preparation. Together with measurements using specific inhibitors, we conclude that the antidiarrheal actions of Krisanaklan include inhibition of luminal CFTR and Ca(2+)-activated Cl(-) channels in enterocytes. HPLC fractionation indicated that the three Cl(-) inhibition actions of Krisanaklan are produced by different components in the herbal extract. Testing of individual herbs comprising Krisanaklan indicated that agarwood and clove extracts as primarily responsible for Cl(-) channel inhibition. The low cost, broad antidiarrheal efficacy, and defined cellular mechanisms of Krisanaklan suggests its potential application for antisecretory therapy of cholera and other enterotoxin-mediated secretory diarrheas in developing countries.